Humanity Can Still Stop Climate Change by Implementing a New International Climate Agreement and Applying Radical New Technology - Zvonimir Glasnovic; Karmen Margeta; Nataša Zabukovec Logar (Energies, 2020)
There is a broad consensus worldwide that anthropogenic climate change is a scientific fact. Likewise, the fact is that the UN’s efforts to address climate change over the last 28 years have not been successful enough. It is evident that the global average temperature is on the rise (1.1 °C above pre-industrial levels in 2019). A particular concern comes from the fact that the Paris Agreement on keeping increases in the global average temperature to below +2 °C is an unenforceable ambition, since the focus is more on consequences than causes. In addition, economic policies regarding global taxes, as well as adaptation and mitigation measures, are questionable, as there is no evidence that changes in the climate system will proceed at the same rate in the coming years. This paper proposes an engineering approach that considers all relevant aspects of the climate change problem and proposes a new policy, named the “Climate New Deal”. It deals with: (i) Reorientation from a high-carbon economy to a green economy; (ii) The intensive use of radically new technology, e.g., “Seawater Steam Engine” technology for the simultaneous production of thermal and electric energy and drinking water; and (iii) The intensive use of energy efficient technologies and RES technologies, especially in transport.